Graphene-embedded LiMn0.8Fe0.2PO4 composites with promoted electrochemical performance for lithium ion batteries. (20th June 2018) - Wen, Fang; Lv, Tu'an; Gao, Ping; Wu, Bing; Liang, Qianqian; Zhang, Yuanyuan; Shu, Hongbo; Yang, Xiukang; Liu, Li; Wang, Xianyou
Abstract: Electron transfer and lithium ion diffusion rates are the key factors leading to sluggish electrochemical kinetics of LiMn0.8 Fe0.2 PO4 . In this work, we have successfully synthesized graphene-embedded LiMn0.8 Fe0.2 PO4 composites via a facile graphene oxide assisted solvothermal route associated with carbonthermal treatment. The effect of graphene on the morphology, crystalline structure as well as electrochemical properties of LiMn0.8 Fe0.2 PO4 is investigated. It can be found that the introducing graphene can reduce the particle size to form LiMn0.8 Fe0.2 PO4 nanocrystals without destroying the crystalline structure of LiMn0.8 Fe0.2 PO4 . And the LiMn0.8 Fe0.2 PO4 nanocrystals dispersed on the graphene sheets which were further cross-linked via the oxygen-containing groups of GO as cross-linking sites, resulting in that graphene sheets embedded in the LiMn0.8 Fe0.2 PO4 composites. Benefiting from the LiMn0.8 Fe0.2 PO4 nanocrystal and embedded graphene, the interconnected conducting network referred to electron and lithium ion transport pathways can be improved, resulting in enhanced electrochemical performance. The graphene embedded LiMn0.8 Fe0.2 PO4 composite displays a high discharge capacity of 163.5, 149.2, 136.0, 120.6, 100.1 and 84.5 mA h g -1 at various rate of 0.1C, 0.5C, 1C, 2C, 5C and 10C, respectively. Meanwhile, it still maintains a reversible capacity of around 120 mA h g -1 after 100 cycles at a rate of 1C.